2010
DOI: 10.1143/jjap.49.09mc11
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectricity of Poly(L-lactic Acid) Composite Film with Stereocomplex of Poly(L-lactide) and Poly(D-lactide)

Abstract: The piezoelectricity of a film of the eco-material poly(L-Lactic acid) (PLLA) with high transparency and flexibility has been noted for its possibility of application to new types of devices used in mobile equipment. However, for its application, there are many difficult problems to be solved, because the PLLA film has poor thermal stability. To change the high-order structure of the PLLA film, thus realizing an improvement in the temperature dependence of its piezoelectricity, a composite film with a stereoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 19 publications
1
36
1
Order By: Relevance
“…The electrospinning process can also align the CO bond to create piezoelectric PLLAs as seen in Figure d (right). PLLA is a transparent and very flexible plant‐derived polymeric material, and is considered suitable for applications in mobile devices as an environmentally friendly, flexible, transparent, piezoelectric thin film . However, the practical application of PLLA is limited because its piezoelectric constant is much lower than that of inorganic piezoelectric materials such as PZT.…”
Section: Mechanisms Of Piezoelectricity In Inorganic and Organic Matementioning
confidence: 99%
“…The electrospinning process can also align the CO bond to create piezoelectric PLLAs as seen in Figure d (right). PLLA is a transparent and very flexible plant‐derived polymeric material, and is considered suitable for applications in mobile devices as an environmentally friendly, flexible, transparent, piezoelectric thin film . However, the practical application of PLLA is limited because its piezoelectric constant is much lower than that of inorganic piezoelectric materials such as PZT.…”
Section: Mechanisms Of Piezoelectricity In Inorganic and Organic Matementioning
confidence: 99%
“…Yoshida et al reported a slight improvement in the piezoelectric modulus (d 0 ) below T g (65-70 1C) in a PLLA composite film with only 10% SC crystals. 42 We have thus looked at the effect of [Ch][DHP] on the piezoelectric response of the membranes measured using piezoresponse force microscopy (PFM). No local piezoelectric activity is observed in PLA (Fig.…”
Section: Piezoelectric Responsementioning
confidence: 99%
“…PLLA does not exhibit pyroelectricity because it does not have an intrinsic polarization. [16][17][18][19][20][21][22] PVDF is a polymer that belongs to the ferroelectric group, and exhibits pyroelectricity because it has an intrinsic polarization. Figure 2 shows the time dependence of the amount of electric charge generated in PLLA and PVDF films due to heat.…”
Section: Pyroelectricity Of the Piezoelectric Filmmentioning
confidence: 99%